The influence of artificial wind blow on the pollination and fructification of blackcurrant (Ribes nigrum L.) cultivars - Bożena Denisow (Acta Scientiarum Polonorum: Hortorum Cultus, 2004)
The experiment of the additional blow of bushes of 8 cultivars of blackcurrant (Ribes nigrum L.) was conducted in 1995–1997 in Pulawy, Poland. The artificial wind blow generated by the vacuum cleaner fan was used. The additional blow of freepollinated and isolated bushes did not caused better pollination of flowers and did not have any positive effect on the weight of 100 fruits, the yield structure or the number of seeds per fruit.